THEORETICAL ASPECTS OF OBTAINING OXIDATION-STABLE VEGETABLE OILS - Yulchiev, Aslbek; Zufarov, Oybek; Isroilova , Shoira; Serkayev, Kamar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The purpose of the research was to theoretically substantiate the principles of oxidation and directions in the development of ways to prevent the appearance of derivatives of oxidation of vegetable oils based on existing modern concepts and patterns. The article substantiates the sequence of oxidation stages and the factors influencing the intensity of the process. The authors, relying on the results of numerous studies conducted by scientists, argue that high-temperature treatment in the presence of enzymes, metal ions, phospholipid residues and various pigments, especially in a relatively humid environment, is a very important component in initiating the process of autooxidation of fatty acids. It is noted that inhibition or at least reduction of the factors of initiation of the primary oxidation process by forrafination in the presence of highly effective reagents leads to an increase in the shelf life of vegetable oils.